2016
DOI: 10.1016/j.nedt.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Integrated systematic review on educational strategies that promote academic success and resilience in undergraduate indigenous students

Abstract: There was a gap in current research evaluating strategies to improve indigenous student success and resilience. Key strategies for indigenous student success are multi-faceted, layered support, underpinned by the principles of respect, relationships, and responsibility. Implications for nursing and midwifery education, research and health care practice are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 19 publications
4
33
0
11
Order By: Relevance
“…The findings from this review concur with Milne et al. () in establishing that attrition for this subset of students is multifaceted, and a variety of support was often required to address retention issues. However, having access to effective support systems (both academic and pastoral) has been demonstrated to have a positive effect on retention both in the qualitative and quantitative studies included in the review.…”
Section: Discussionsupporting
confidence: 87%
“…The findings from this review concur with Milne et al. () in establishing that attrition for this subset of students is multifaceted, and a variety of support was often required to address retention issues. However, having access to effective support systems (both academic and pastoral) has been demonstrated to have a positive effect on retention both in the qualitative and quantitative studies included in the review.…”
Section: Discussionsupporting
confidence: 87%
“…47 Through an integrated qualitative review, Milne and colleagues found that cultural, financial, and academic support were necessary components for resilience in indigenous nursing students. 48 In another integrated review, Reyes and colleagues identified protective factors as being associated with resilience and the ability to buffer or mitigate risk factors. Reyes and colleagues assert that strategies should be explored and implemented to enhance protective factors.…”
mentioning
confidence: 99%
“…La función de este tipo de educación es capacitar individuos para el mundo del trabajo e impartir ideologías que se supone son deseables para la sociedad moderna, invisibilizando las necesidades propias del contexto caracterizado por la diversidad social y cultural (Atta-Alla, 2012;Olivera, 2013). La reproducción de la monoculturalidad en los espacios de educación, reproduce conductas discriminatorias excluyentes y racistas, explicitas o implícitas, entre las relaciones de los diferentes actores educativos (Carignan, Sanders, & Pordavood, 2005;Mampaey & Zanoni, 2015;Veldman & Guilfoyle, 2013) Dichas tensiones podrían eventualmente conducir a los estudiantes a un fracaso académico (Milne, Creedy, & West, 2016) frustración de los profesores y de los estudiantes (Bishop, Berryman, Wearmouth, Peter, & Clapham, 2012), conflictos personales, académicos y sociales (Watson & cols., 2002), crisis en su identidad cultural (Cook-Sather, 2015) y una baja tasa de retención de estudiantes pertenecientes a los grupos minoritarios (Chirgwin, 2015).…”
Section: Introductionunclassified
“…Existen diversos factores que se han conjugado para hacer de la experiencia universitaria un escenario más complejo y tensionante para los estudiantes pertenecientes a grupos originarios (Brunner, 2015). Dichas tensiones pueden surgir, desde la perspectiva del estudiante, por factores académicos relacionados con el desarrollo de competencias básicas previas al ingreso a la universidad (Hall, 2012), por el tipo de apoyo académico que pueda ofrecer la institución (Milne, Creedy, & West, 2016), pero también con dimensiones socio-afectivas relacionadas con discriminación y racismo Institucional, de los profesores o de sus pares que no pertenecen a grupos originarios (Oliver & cols., 2013) Por otro lado, desde la Universidad como institución educativa, las tensiones surgen por aspectos administrativos, cambios legales y proyecciones curriculares que responden a las exigencias del contexto nacional y que no siempre logran responder a las necesidades del contexto local respecto a diversidad social y cultural (Wit, 2011). En efecto, las instituciones universitarias reconocen la diversidad social y cultural de sus estudiantes desde una perspectiva funcional, estadística y política, generando rutas de acceso a la Educación Superior y posibilidades de acceso a estudianposibilidades de acceso a estudiantes que tradicionalmente no ingresaban a la universidad, como es el caso de los estudiantes mapuches (Arancibia, Guerrero, Hernández, Maldonado, & Román, 2014).…”
unclassified
See 1 more Smart Citation